Importance of oral dosing rate on the hemodynamic and pharmacokinetic profile on nilvadipine - Cheung, W K; Sia, L L; Woodward, D L; Graveline, J F; Desjardins, R E; Yacobi, A; Silber, B M (Journal of clinical pharmacology, 1988)
Nilvadipine was administered as an oral solution formulation to 12 normotensive subjects in a three-way randomized crossover study at a dose of 16 mg as three different dosing regimens: 1) as a single 16 mg dose, 2) as a 1.6 mg dose given hourly for 10 doses, and 3) as an initial dose of 4.8 mg, followed by 1.6 mg doses given every hour for seven additional doses. After each dose, clinical effects, hemodynamic changes and the pharmacokinetic profile of the drug were determined. The mean maximum changes in diastolic (DBP) and systolic (SBP) blood pressure and heart rate (HR) after dosing regimens 1, 2, and 3 were: -33, -13 and +46%; -17, -14 and +38%; and -24, -14 and +36%, respectively. There was a relationship between the changes in DBP and HR and plasma concentrations of nilvadipine only after dosing regimen 1. The effect-concentration relationships were fit to a modified Emax model. There was no relationship between the change in SBP and plasma concentration after any of the dosing regimens. While there were no significant differences in the mean area under the plasma concentration-time curve (AUC0---infinity) between dosing regimens 2 (38.7 ng.hr/mL) and 3 (42.1 ng.hr/mL) (P greater than 0.05), the mean AUC0---infinity after regimen 1 (76.3 ng.hr/mL) was significantly greater than after dosing regimens 2 or 3 (P less than 0.05). The mean maximal plasma concentrations (Cmax) were 31.6, 1.3 and 6.3 ng/mL after dosing regimens 1, 2 and 3, respectively.